Soji Project: Virtual Campaign And Distribution Of Hand Sanitizer From Local Commodities To Street Vendors - Asri Widyasanti; Angela A. Lasut; Fani R. Rahmani; M. Ridwan Rais; Nurhanifah Puspitadewi; Rangga Novandra (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
The SOJI project is one of activity dealing with community empowering and services with the topic "Training on Local Commodity-Based Hand Sanitizers and Natural Disinfectants". This activity is carried out virtually using online media because it is in a pandemic era and is required to carry out remote activities to reduce social contact. SOJI has three main activities in the form of a virtual campaign which is carried out by educating the public about hand sanitizers through social media, making hand sanitizers natural ingredients from local commodities in each student residence, and distributing hand sanitizers made from natural local commodities for free while also educating the importance of cleanliness hand to the street vendors (PKL). The purpose of this activity is to first increase the knowledge and awareness of street vendors and the community about the importance of using hand sanitizer as an alternative to maintaining hand hygiene, secondly to provide information to the community on how to make hand sanitizers made from natural local commodities. The benefit of this activity is to educate street vendors and the general public so that they are more aware of the use of hand sanitizers as an alternative to hand hygiene supervision and the community can make hand sanitizers made from natural local commodities. The achievement obtained from the virtual campaign was the total number of likes in the form of infographics (4 contents) were 912 likes, while two video contents reached 1171 total views over 1 month period.